Experiência vivida no tratamento do transtorno afetivo bipolar: um estudo fenomenológico. - Andressa Fraga Sant'Ana Alves Novais (2023)
Mental health problems generate psychological suffering, affecting behaviors, thoughts, perceptions and feelings, changes that have repercussions on interpersonal relationships, both in family life and at work. Bipolar Affective Disorder has a worldwide prevalence of over 45 million people. It is a chronic mental health problem, characterized by severe mood changes, episodes of depression, negative mood, mania (exacerbated mood) or hypomania. The clinical management of this health condition involves several measures to establish the care process, such as pharmacological treatment, psychotherapies, psychoeducational measures and multidisciplinary monitoring. The most commonly prescribed medications for treatment are mood modulators such as lithium and atypical antipsychotics such as risperidone. This qualitative research was developed using Max van Manen's method, Phenomenology of Practice, with the aim of revealing the patient's lived experience in pharmacological treatment for the treatment of Bipolar Affective Disorder. To collect data, individual semistructured interviews and focus groups were carried out. Data processing used the thematic analysis technique, facilitated by NVivo Software. The results revealed five themes: “Before and after diagnosis”, “Mental health recovery is subjective”, “Living like Alice: difficulty in achieving balance”, “Medicine helps, but does not perform miracles” and “Before and after the most effective medicine.” The research contributed to understanding the experience lived by patients with medications, for a more effective mental health recoveryprocess.